Strategic Evaluation of Financial Information Systems through Information Technology Auditing - Bakri, Asri Ady; Alfiah, Agry (PT.KARYA GEMAH RIPAH, 2024)
People-based cooperatives encounter digital hurdles to providing effective services. Wiguna Mertha Cooperative needs IT audits to ensure good operations, security, and corporate goals. Enterprise information technology audits are conducted using qualitative and quantitative methodologies in this research. IT audit goal mapping helps firms align business goals with corporate goals, vision, purpose, and IT procedures. PEG aligns IT investments and activities with company strategy, evaluates IT maturity, and prioritizes improvements. Interviews, questionnaires, observations, and documentation were used to analyze 5 cooperative employees' responses. Objective mapping for five corporate goals and maturity level analysis for four COBIT domains: EDM, APO, BAI, and DSS. The results revealed good maturity, with EDM averaging 3.85, APO 3.87, BAI 3.88, and DSS 3.53. Risk management, business resource optimization, IT data up keep, and IT service availability and capacity management are recommended improvements.